Inequalities in prevalence of birth by caesarean section in Ghana from 1998-2014 - Joshua Okyere; Henry Ofori Duah; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Eugene Budu (BMC, 2022)
Abstract Background Caesarean section (CS) is an intervention to reduce maternal and perinatal mortality, for complicated pregnancy and labour. We analysed trends in the prevalence of birth by CS in Ghana from 1998 to 2014. Methods Using the World Health Organization's (WHO) Health Equity Assessment Toolkit (HEAT) software, data from the 1998-2014 Ghana Demographic and Health Surveys (GDHS) were analysed with respect of inequality in birth by CS. First, we disaggregated birth by CS by four equity stratifiers: wealth index, education, residence, and region. Second, we measured inequality through simple unweighted measures (Difference (D) and Ratio (R)) and complex weighted measures (Population Attributable Risk (PAR) and Population Attributable Fraction (PAF)). A 95% confidence interval was constructed for point estimates to measure statistical significance. Results The proportion of women who underwent CS increased significantly between 1998 (4.0%) and 2014 (12.8%). Throughout the 16-year period, the proportion of women who gave birth by CS was positively skewed towards women in the highest wealth quintile (i.e poorest vs richest: 1.5% vs 13.0% in 1998 and 4.0% vs 27.9% in 2014), those with secondary education (no education vs secondary education: 1.8% vs 6.5% in 1998 and 5.7% vs 17.2% in 2014) and women in urban areas (rural vs urban 2.5% vs 8.5% in 1998 and 7.9% vs 18.8% in 2014). These disparities were evident in both complex weighted measures of inequality (PAF, PAR) and simple unweighted measures (D and R), although some uneven trends were observed. There were also regional disparities in birth by CS to the advantage of women in the Greater Accra Region over the years (PAR 7.72; 95% CI 5.86 to 9.58 in 1998 and PAR 10.07; 95% CI 8.87 to 11.27 in 2014). Conclusion Ghana experienced disparities in the prevalence of births by CS, which increased over time between 1998 and 2014. Our findings indicate that more work needs to be done to ensure that all subpopulations that need medically necessary CS are given access to maternity care to reduce maternal and perinatal deaths. Nevertheless, given the potential complications with CS, we advocate that the intervention is only undertaken when medically indicated.